TENSÕES PARADOXAIS DE SUSTENTABILIDADE: ANÁLISE QUALITATIVA A PARTIR DA ABORDAGEM QU NTICA DO PARADOXO ORGANIZACIONAL - Izabela Leite Ribeiro Guimaraes (2023)
The paradoxical tensions arise from the pursuit of conflicting yet interrelated objectives, which can be studied from the perspective of inherent and/or constitutive approaches. The organizational paradox theory from the perspective of the quantum approach - AQ was used in this study because it seeks a possible path to reconcile such perspectives, aiming to understand the reality underlying paradoxical tensions. In this sense, the overall objective of the thesis is to understand the dynamics of sustainability paradoxes in paper and pulp companies from the perspective of AQ organizational paradox. To achieve this, a qualitative research was conducted with eight companies in the sector, which disclose reports following the GRI model and/or are listed on the B3. Data were collected following a protocol, and the interviews were guided by a semi-structured script. Sustainability reports, management plans, and news about the companies were analyzed using inductive and deductive logics with the assistance of Atlas.ti. The results provide insight into the socio-material context of each company, prominent paradoxical tensions, the nexus of intertwined and persistent tensions, as well as organizational responses to tensions. Understanding the socio-material context made it possible to identify tensions still in a latent state, not captured in organizational discourse, and performance tensions observed in greater numbers, justified by the pursuit of meeting multiple concurrent demands. Additionally, a strong relationship between learning and organizational tensions was observed, given the recurring observation of these typologies in an entanglement configuration. Entangled tensions emerged in three distinct forms: (1) cascading tensions, materialized through two quotations, one implying the other; (2) grouped tensions, identified in a single quotation; and (3) tensions embedded in organizational responses, indicating a tendency not to propagate bad news. The analysis to identify prominent tensions proved challenging given this tendency but was fundamental to practically applying AQ assumptions. The fragility of salience could be empirically tested through a specific analysis cut during the COVID-19 period, where tensions characteristic of a crisis context emerged. The analysis prompted reflection on the subjectivity of salience, implying a myriad of prominent tensions or, conversely, tensions may not be promulgated. In the former case, over time, it may hinder an analysis of the persistence of paradoxical tensions. In the latter, given another ontological implication, uncertainty, certain organizational issues may be seen as paradoxical or not, depending on their promulgation, raising relevant questions for sustainability management practice. Regarding responses to tensions, two types were more commonly found: (1) punctual responses, where the effort seems to be less compared to the gains from the action; and (2) grounded responses, where the organization invests more effort through practices such as research, stakeholder consultations, action plans, and process reformulation. However, even with organizational responses, companies experienced persistent tensions. Most configurations of entangled and persistent tensions revolved around a key resource for the sector, water. Entangled configurations of persistent paradoxes were observed in four of the eight analyzed companies. The configuration of the socio-material context enables an understanding of tension dynamics and makes interactions with the environment apparent, marking a multilevel analysis perspective that can bring sustainability gains. For management, it allows curation of tensions in their different phases, reflecting different roles for managers. The results of this study show that managing the persistence phase of tensions can be the most complex. Additionally, the study's results point to issues that go beyond theoretical and applied boundaries, reflecting on strategic tools in the pursuit of sustainability.